CROWD PSYCHOLOGY, FEATURES OF PREVENTING MASS RIOTS - Gozibekov Tolkin Khabibullaevich (Web of Journals Publishing, 2024)
This article examines issues related to ensuring public safety during mass events, issues related to the emergence of various serious conflicts, ensuring interethnic disputes in international relations, preventing violations and monitoring offenders.
Keywords: Mass riots, political, economic, social, ethnic, religious, environmental, as a result of illegal actions of police officers and the scene of the incident, populated areas, correctional institutions, duration and long-term, episodic and participants.